Nearpod-Based Animation Video Media on Increasing Learning Motivation and Understanding of Ecosystem Concepts in Elementary Schools - Yulia Anggraeni; Abdul Muis; Rina Sugiarti Dwi Gita (Universitas Pendidikan Ganesha, 2025)
Learning motivation and conceptual understanding among elementary school students are still considered low. Difficulties in concentrating and understanding abstract material are factors that hinder the achievement of learning objectives. This study aims to analyze the effectiveness of using Nearpod-based animated video media in improving learning motivation and conceptual understanding of ecosystems among elementary school students. This research employed a quantitative approach with a quasi-experimental design using the one-group pretest-posttest method. The research subjects consisted of 20 students, who also served as trial participants. Data were collected through a learning motivation questionnaire and a conceptual understanding test that had been validated and tested for reliability. Data analysis was conducted using the non-parametric Wilcoxon Signed-Rank test because the data were not normally distributed. The results of the study showed that the use of Nearpod-based animated videos was effective in enhancing learning motivation while strengthening students’ conceptual understanding of ecosystems. Thus, this media can be concluded as an innovative and meaningful learning tool to address low learning motivation and difficulties in understanding abstract concepts among elementary school students. The implications of this study emphasize the importance of utilizing interactive learning technologies to create engaging, concrete, and supportive learning experiences in achieving educational goals.